Physicochemical Characteristics of Watermelon (Citrullus lanatus) Peel Kombucha as Influenced by Fermentation Duration - Difa Najwa Rashifah; Ambarwati Ambarwati (Bioscientist : Jurnal Ilmiah Biologi, 2026)
This study aimed to determine the physicochemical characteristics of watermelon rind (Citrullus lanatus) kombucha, including antioxidant activity, vitamin C content, pH, and alcohol content, based on variations in fermentation duration. The findings were used to identify the most effective fermentation period for producing a beverage rich in natural antioxidants while adding value to agro-industrial waste utilization. This quantitative experimental study employed a single-factor completely randomized design (CRD) with two replications. The fermentation periods were 8, 10, and 12 days. Physicochemical analyses included antioxidant activity using the DPPH method, vitamin C content using iodometric titration, alcohol content using an alcohol meter, and pH measurement using a pH meter. Data were analyzed using the Kruskal–Wallis test, followed by Duncan’s test to compare the effectiveness of fermentation treatments. The results showed that 10 days of fermentation produced the highest physicochemical characteristics, with antioxidant activity of 49.26 ± 0.11c, vitamin C content of 75.49 ± 1.50b, pH of 4.14 ± 0.35a, and alcohol content of 0.6 ± 0.00c. However, the alcohol content on day 10 exceeded the safe limit for beverage products; therefore, this treatment is not recommended for consumption. In contrast, the 8- and 12-day fermentation treatments produced physicochemical characteristics with alcohol levels within the safe limit. On day 12, the antioxidant activity was 45.66 ± 0.11b, vitamin C content was 64.42 ± 1.49b, pH was 3.99 ± 0.31a, and alcohol content was 0.4 ± 0.00a. On day 8, the antioxidant activity was 43.54 ± 0.11a, vitamin C content was 67.48 ± 3.07a, pH was 4.59 ± 0.02a, and alcohol content was 0.5 ± 0.00b. Overall, although the 10-day fermentation treatment yielded superior physicochemical properties, the 8- and 12-day treatments are more recommended because their alcohol contents remained within the safe limit.